Pengaruh Beauty Influencer dan Kualitas Produk Terhadap Keputusan Pembelian Produk Scarlett Whitening pada Sosial Media - V, Velicia; Amelda, Jesinta Tria (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine the influence of quality and product quality on purchasing decisions for beauty products on social media. The sampling used in this research was a purposive method and non-probability technique with a sample size of 100 respondents. The data used is primary data. The data analysis techniques used are validity test, reliability test, classical regression test, multiple regression analysis, hypothesis analysis using the SPSS program and coefficient of determination. The results of this research show that the influence of beauty quality has a positive and significant influence on decisions to purchase beauty products on social media, while product quality does not have a significant influence on decisions to purchase beauty products on social media.